Effect of blending process on rheological and volumetric properties of asphalt binder - Solouki, Abbas (2015)
The improvement of asphalt binder physical properties is possible through the addition of polymers. However, due to different physical and chemical properties of additives, each modifier requires its unique blending processing conditions. Despite these facts, not much attention has been paid to the effects of blending process on the rheological properties of asphalt binders. Therefore, it was hypothesized that different blending parameters could affect the rheological properties of asphalt binders, which in turns influence the overall performance of polymer modified blends and mixtures. As a result, three different objectives were set for the current study which were 1) to establish a blending matrix for asphalt binder modification, 2) to determine the effect of blending process on the rheological properties of asphalt binders, and 3) to determine the effect of blending process on the volumetric properties of asphalt mixtures. The blending matrix was established by selecting different parameters which potentially affected the blending outcome and the modified binders were prepared according to the established matrix. Different binder tests including softening point temperature, rotational viscosity, and dynamic shear rheometer (DSR) tests were conducted on EVA and Sasobit modified binders. Finally, the optimum asphalt content of mixtures was obtained for samples prepared at three different motor speed values of 400, 1200, and 1800 using the two mentioned polymers. The results indicated high binder stiffness for binders processed at higher blending speeds compared to binders blended at lower speeds. This was observable through higher softening point temperatures, higher viscosity values,and higher complex modulus measurements. Therefore, an increase in motor speed values increased the overall stiffness of the modified binders. Additionally,the stiffness of asphalt binders also increased with an increase in additive content. Likewise, the optimum asphalt binder content increased for mixtures containing stiffer binders. It was concluded that an increase in motor speed preaged the binder sample during the preparation process which led to its increased stiffness. It has to be mentioned that the pre-aging phenomena is undesirable since it will reduce the overall service life of pavements. The application of lower motor speed during blending is highly suggested.